2007
DOI: 10.1016/j.chom.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Host Glycoprotein Gp96 and Scavenger Receptor SREC Interact with PorB of Disseminating Neisseria gonorrhoeae in an Epithelial Invasion Pathway

Abstract: Neisseria gonorrhoeae expresses numerous surface proteins that mediate bacterial adherence and invasion during infection. Gonococci expressing serotype A of the major outer membrane porin PorB (PorB(IA)) are frequently isolated from patients with severe disseminating infections. PorB(IA) triggers efficient adherence and invasion under low phosphate conditions mimicking systemic bloodstream infections. Here, we identify the human heat shock glycoprotein Gp96 and the scavenger receptor SREC as PorB(IA)-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 48 publications
0
75
0
1
Order By: Relevance
“…Many results concerning the ability of pathogens expressing ChoP to invade human cells were related to different species and even different compartments from the same bacteria (10,11,38). Here, we showed that ChoP was present in OMPs of A. baumannii.…”
Section: Discussionmentioning
confidence: 56%
“…Many results concerning the ability of pathogens expressing ChoP to invade human cells were related to different species and even different compartments from the same bacteria (10,11,38). Here, we showed that ChoP was present in OMPs of A. baumannii.…”
Section: Discussionmentioning
confidence: 56%
“…TmpC is hypothesized to be involved in purine transport (25), so it is possible that BmpA may perform such a role for B. burgdorferi. Dual-function outer surface proteins, such as the B. burgdorferi p66 porin/integrin adhesin, the subgroup of B. burgdorferi Erp proteins that bind host plasminogen and complement factor H, and the Neisseria gonorrhoeae PorB porin/adhesin, are not uncommon in bacteria (1,12,23,37,40,43,54,57,67,71).…”
Section: Resultsmentioning
confidence: 99%
“…While SCARF1 was first shown to bind acetylated LDL, SCARF1 is also an endocytic receptor for calreticulin, gp96 and Tamm-Horsfall protein. [48][49][50][51] In addition to recognizing these endogenous host proteins, SCARF has also been shown to bind and internalize Neisseria gonorrhoeae bacterium via its interaction with gp96. 50 Similar to SCARF1, CD36 is a cell surface receptor with broad ligand specificity for endogenous (modified LDL, thrombospondin, apoptotic cells) 52 and pathogenic (Plasmodium falciparum, mycobacterial lipopepitde, Staphylococcus aureus) ligands.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51] In addition to recognizing these endogenous host proteins, SCARF has also been shown to bind and internalize Neisseria gonorrhoeae bacterium via its interaction with gp96. 50 Similar to SCARF1, CD36 is a cell surface receptor with broad ligand specificity for endogenous (modified LDL, thrombospondin, apoptotic cells) 52 and pathogenic (Plasmodium falciparum, mycobacterial lipopepitde, Staphylococcus aureus) ligands. 15,53 It has recently become appreciated that the specificity of TLR signaling is regulated, in part, through the association of TLRs with cell surface co-receptors.…”
Section: Discussionmentioning
confidence: 99%